Regional Heterogeneity of Length–Tension Relationships in Rat Lymph Vessels - Gashev, Anatoliy A. (Mary Ann Liebert, Inc., 2012)
BACKGROUND: Heterogeneity of the length–tension relationships in lymph vessels has never been evaluated systematically. METHODS AND RESULTS: In this study we measured the length–tension relationships in lymph vessels from three different regions of the rat: thoracic duct, cervical, and femoral lymph vessels, and compared the results to our previous measurements of rat mesenteric lymph vessels. We performed isometric force measurements on activated and passive lymph vessel segments using a small-vessel wire myograph. We found that all groups of vessels had relatively broad plateaus in their active tension versus length relationships, suggesting that they are adapted to generate near-maximal tensions over a relatively wide range of preloads (at least 0.85–1.05 L(0)). Thoracic duct exhibited the flattest active tension curve, particularly for peak active tension, in which there was less than a 5% change in peak active tension from 0.75 to 1.30 of optimal length. Femoral lymph vessels were able to withstand the highest estimated pressures, followed by mesenteric and cervical vessels and then thoracic duct. CONCLUSIONS: We conclude that lymph vessels effectively adapt their contractile force to the particular hydrodynamic conditions (transmural pressures and intraluminal flows) that exist in different regions of the lymphatic system.